Burkitt lymphoma expresses oncofetal chondroitin sulfate without being a reservoir for placental malaria sequestration. Issue 7 (6th February 2017) - Agerbæk, Mette Ø.; Pereira, Marina A.; Clausen, Thomas M.; Pehrson, Caroline; Oo, Htoo Zarni; Spliid, Charlotte; Rich, Jamie R.; Fung, Vincent; Nkrumah, Francis; Neequaye, Janet; Biggar, Robert J.; Reynolds, Steven J.; et al.
Abstract : Burkitt lymphoma (BL) is a malignant disease, which is frequently found in areas with holoendemic Plasmodium falciparum malaria. We have previously found that the VAR2CSA protein is present on malaria‐infected erythrocytes and facilitates a highly specific binding to the placenta. ofCS is absent in other non‐malignant tissues and thus VAR2CSA generally facilitates parasite sequestration and accumulation in pregnant women. In this study, we show that the specific receptor for VAR2CSA, the oncofetal chondroitin sulfate (ofCS), is likewise present in BL tissue and cell lines. We therefore explored whether ofCS in BL could act as anchor site for VAR2CSA‐expressing infected erythrocytes. In contrast to the placenta, we found no evidence of in vivo sequestering of infected erythrocytes in the BL tissue. Furthermore, we found VAR2CSA‐specific antibody titers in children with endemic BL to be lower than in control children from the same malaria endemic region. The abundant presence of ofCS in BL tissue and the absence of ofCS in non‐malignant tissue encouraged us to examine whether recombinant VAR2CSA could be used to target BL. We confirmed the binding of VAR2CSA to BL‐derived cells and showed that a VAR2CSA drug conjugate efficiently killed the BL‐derived cell lines in vitro . These results identify ofCS as a novel therapeutic BL target and highlight how VAR2CSA could be used as a tool for the discovery of novel approaches for directing BL therapy. Abstract : What's new? Co‐infection by Epstein–Barr virus and the malarial parasite Plasmodium falciparum is a suspected etiological factor in endemic Burkitt lymphoma (BL). Meanwhile, oncofetal chondroitin sulfate (ofCS), a binding anchor for VAR2CSA‐expressing Plasmodium ‐infected erythrocytes in the placenta, is expressed in diverse types of tumors. This study shows that ofCS is also expressed in BL tissue, though it does not serve a role in the sequestration of infected erythrocytes. In vitro, BL cells were successfully targeted and killed by a malaria‐derived VAR2CSA drug conjugate, suggesting that ofCS expression could be leveraged to deliver a toxic payload to BL tissue.